Occult hepatitis B virus infection in patients with chronic liver disease of different etiology in a Brazilian referral center: comparison of two different hepatitis B virus deoxyribonucleic acid amplification protocols: a cross-sectional study - Ferrari, Teresa Cristina Abreu; Faria, Alessandra Coutinho de; Vidigal, Paula Vieira Teixeira; Correa, Bernardo Henrique Mendes; Faria, Luciana Costa; Xavier, Marcelo Antônio Pascoal (São Paulo Medical Journal, 2023)
BACKGROUND: Occult hepatitis B virus infection (OBI) is defined as the presence of hepatitis B virus (HBV) deoxyribonucleic acid (DNA) in the liver of individuals with undetectable hepatitis B virus surface antigen (HBsAg) in the serum. The actual prevalence of OBI and its clinical relevance are not yet fully understood. OBJECTIVE: To evaluate the prevalence of HBV DNA in liver biopsies of HBsAg-negative patients with chronic liver disease of different etiologies in a referral center in Brazil and compare two different HBV DNA amplification protocols to detect HBV. DESIGN AND SETTING: This cross-sectional observational study was conducted at the Liver Outpatient Clinic, Hospital das Clínicas, Universidade Federal de Minas Gerais, Belo Horizonte, MG, Brazil, between January 2016 and December 2019. METHODS: HBV DNA was investigated in 104 liver biopsy samples from individuals with chronic liver disease of different etiologies, in whom HBsAg was undetectable in serum by nested-polymerase chain reaction (nested-PCR), using two different protocols. RESULTS: OBI, diagnosed by detecting HBV DNA using both protocols, was detected in 6.7% of the 104 individuals investigated. Both protocols showed a good reliability. CONCLUSION: In addition to the differences in the prevalence of HBV infection in different regions, variations in the polymerase chain reaction technique used for HBV DNA amplification may be responsible for the large variations in the prevalence of OBI identified in different studies. There is a need for better standardization of the diagnostic methods used to diagnose this entity.